Diagnosis, Classification and Management of Black Sodic Soils :An Overview: Classification and management of black sodic soils - Kharche, V. K.; Paradhi, Anjali; A. O. Shirale; Jadhao, S.D. (Journal of Soil Salinity and Water Quality, 2024)
Black sodic soils pose a significant challenge in agricultural production, particularly in arid and semi-arid regions where high sodium content degrades soil structure and fertility. These soils suffer from nutrient deficiencies, poor physical properties, and increased susceptibility to erosion, leading to reduced crop productivity and economic losses. Sodicity is exacerbated by poor irrigation practices and the rising demand for water. This review explores the characteristics, diagnosis, and classification of black sodic soils, alongside strategies for their sustainable management, focusing on amelioration techniques such as the use of soil amendments and organic materials.